VD_FINDINFO Plainte / 2020 / 35 vom 2. November 2020 - VD Tribunal cantonal (2020)
BAIL À LOYER, SÛRETÉS, CRÉANCE GARANTIE PAR GAGE, GARANTIEGAGE, DROIT D'ÊTRE ENTENDU, PAIEMENT | 257e CO, 17 LP, 41 al. 1 LP, 41 al. 1bis LP, 53 CPC (CH)